2010
DOI: 10.1111/j.1365-313x.2010.04253.x
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis thaliana FPP synthase isozymes have overlapping and specific functions in isoprenoid biosynthesis, and complete loss of FPP synthase activity causes early developmental arrest

Abstract: SUMMARYFarnesyl diphosphate (FPP) synthase (FPS) catalyses the synthesis of FPP, the major substrate used by cytosolic and mitochondrial branches of the isoprenoid pathway. Arabidopsis contains two farnesyl diphosphate synthase genes, FPS1 and FPS2, that encode isozymes FPS1L (mitochondrial), FPS1S and FPS2 (both cytosolic). Here we show that simultaneous knockout of both FPS genes is lethal for Arabidopsis, and embryo development is arrested at the pre-globular stage, demonstrating that FPP-derived isoprenoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
90
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(92 citation statements)
references
References 63 publications
1
90
1
Order By: Relevance
“…1) are presumed to produce FPP and GGPP for ubiquinone synthesis. FPPS1L-defective fps1 mutants only showed a limited decrease in UB-9 levels (Closa et al, 2010), suggesting that the biosynthesis of the ubiquinone solanesyl chain might predominantly rely on the supply of GGPP by GGPPS1, the only GGPPS isoform known to be targeted to mitochondria (Beck et al, 2013;Nagel et al, 2015). However, we found that the T-DNA insertion mutant ggpps1-1 (SAIL_559_G01) contains wild-type levels of UB-9 (Supplemental Fig.…”
Section: G11 Activity Is Essential To Produce Both Plastidial Isoprencontrasting
confidence: 42%
See 2 more Smart Citations
“…1) are presumed to produce FPP and GGPP for ubiquinone synthesis. FPPS1L-defective fps1 mutants only showed a limited decrease in UB-9 levels (Closa et al, 2010), suggesting that the biosynthesis of the ubiquinone solanesyl chain might predominantly rely on the supply of GGPP by GGPPS1, the only GGPPS isoform known to be targeted to mitochondria (Beck et al, 2013;Nagel et al, 2015). However, we found that the T-DNA insertion mutant ggpps1-1 (SAIL_559_G01) contains wild-type levels of UB-9 (Supplemental Fig.…”
Section: G11 Activity Is Essential To Produce Both Plastidial Isoprencontrasting
confidence: 42%
“…Interestingly, loss of sG11 activity in g11-3 and g11-4 mutants prevents embryo development to proceed beyond the heart stage (Supplemental Fig. S5; Ruiz-Sola et al, 2016), similar to that observed in ubiquinone-defective mutants (Okada et al, 2004), whereas complete loss of FPPS activity in Arabidopsis fps1 fps2 double mutants blocks embryogenesis at the earlier globular stage (Closa et al, 2010). These results suggest that while FPP-derived isoprenoids are needed for the transition of the embryo from globular to heart stages, progression beyond the heart stage requires ubiquinone or/and a different metabolite produced from sG11-supplied precursors.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The existence of a cytosolic IP/DMAP pool suggests that IP and DMAP may serve as FPPS inhibitors in vivo, thus controlling carbon flux toward downstream products. AtFPPS1 is one of two Arabidopsis FPPS genes that is highly expressed in vegetative tissue (22) and shows coexpression with AtIPK (Dataset S1). Data are means ± SD (n = 3 independent experiments).…”
Section: Ipk Contributes To Terpenoid Formation Via Increasing Ipp/dmappmentioning
confidence: 99%
“…Overexpression of FPS1L or FPS1S causes a cell death/senescence-like phenotype due to a metabolic imbalance that impairs cytokinin biosynthesis (Masferrer et al, 2002;Manzano et al, 2006), whereas overexpression of FPS2 has no apparent detrimental effect on plant growth and development (Bhatia et al, 2015). On the other hand, fps1 and fps2 single knockout mutants are almost indistinguishable from wild-type plants, which is in sharp contrast with the embryo lethality of the fps1/fps2 double mutant (Closa et al, 2010). That work and several other studies have demonstrated that normal functioning of the isoprenoid pathway in the cytosol is indispensable for plant viability.…”
mentioning
confidence: 47%